Bioactive compound and therapeutic value of the some Malaysia medicinal plants: A review - Nashriyah, Mat; Mohammad Moneruzzaman, Khandaker; Nik Nurnaeimah, Nik Muhammad Nasir (Asian Network for Scientific Information, 2015)
There are many medicinal plants that have been used since folk ages. These plants have been recognized to have pharmaceutical properties and beneficial impact on health. This study discusses the use of ten medicinal plants in the traditional medicinal system of Malaysia and related scientific on their antioxidant activity, which demonstrate their pharmaceutical properties. The plants viewed are Andrographis paniculata, Cosmos caudatus, Eurycoma longifolia, Ficus deltoidea, Gynura procumbens, Labisia pumila, Orthosiphon stamineus, Phyllanthus niruri, Piper betle and Uncaria gambir. All the plants mentioned in this study have therapeutic properties such as antioxidation, antidiabetics, antiinflammation, which explains and validates their uses in traditional and modern medicine.